Efforts to Improve Learning Outcomes and Motivation to Throw Discs Through Plastic Plate Modification Tools Containing Sawdust in Class IX SMP Negeri 9 Kendari (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2022)
This study aims to (1) find out how the application of a modified plastic plate containing sawdust in improving the results and motivation of learning to throw a discus; and (2) find out whether the application of a modified plastic plate containing sawdust can improve the learning outcomes and motivation of discus throwing in Class IX.2 SMP Negeri 9 Kendari. This research is a classroom action research conducted in the pre-cycle stage through the results of tests and two learning cycles. The stages of each cycle consist of: (1) planning, (2) implementing actions, (3) observing and evaluating, and (4) reflection. Sources of data are students and teachers. So the data analysis in this study was carried out quantitatively and qualitatively using observation sheets and learning outcomes tests. The results showed that there was an increase in the quality of learning to improve results in terms of processes and in terms of learning outcomes, so it was concluded that using a modified plastic plate containing sawdust could increase the results and motivation to learn discus throwing for Class IX.2 semester 1 SMP Negeri 9 Kendari.